Anti-angiogenesis effect of crocous sativus L. extract on matrix metalloproteinase gene activities in human breast carcinoma cells - Mousavi Marzieh; Baharara Javad; Asadi-Samani Majid (Shahrekord University of Medical Sciences, 2014)
Introduction: There is an interest in Crocous sativus L. (Saffron) mainly because of its biological properties. Biomedical research has focused on saffron as a powerful antioxidant, anti-inflammatory and anti-tumor, but its mechanism has not yet been thoroughly clarified. In this study, the effects of saffron aqua extract on matrix metalloproteinases (MMP) gene expression were investigated. Methods: In this experimental study, the saffron was extracted using water as solvent. MCF-7 cells in RPMI1640 medium were supplemented with 10% FBS and incubated at 37 ˚C with 5% CO2. After 24 h, the cells were treated by saffron extract at concentrations of 100, 200, 400 and 800 μg/ml. 48 h after treatment, total RNA was extracted and cDNA was synthesized using specific primer. Synthesized products were analyzed by Real Time PCR to determine expression level of MMP. Results: Data analysis showed inhibitory effect of saffron at concentrations of 100 to 800 μg/ml on MMP gene expression in comparison with control group. Reduction for 100, 200, 400 and 800 μg/ml were 5%, 18%, 15%, 11%, respectively. According to data analysis treating MCF-7 cells with saffron at concentration of 200 μg/ml caused the highest decrease, with 18% reduction in gene expression (P<0.001). Conclusion: Results indicate decrease in the expression of MMP compared with controls revealing induction of inhibitory effects of saffron on angiogenesis which might be also considered as a promising chemotherapeutic agent in breast cancer treatment.